An international review of the patterns and determinants of health service utilisation by adult cancer survivors - Treanor Charlene; Donnelly Michael (BMC, 2012)
Abstract Background There is a need to review factors related to health service utilisation by the increasing number of cancer survivors in order to inform care planning and the organisation and delivery of services. Methods Studies were identified via systematic searches of Medline, PsycINFO, CINAHL, Social Science Citation Index and the SEER-MEDICARE library. Methodological quality was assessed using STROBE; and the Andersen Behavioural Model was used as a framework to structure, organise and analyse the results of the review. Results Younger, white cancer survivors were most likely to receive follow-up screening, preventive care, visit their physician, utilise professional mental health services and least likely to be hospitalised. Utilisation rates of other health professionals such as physiotherapists were low. Only studies of health service use conducted in the USA investigated the role of type of health insurance and ethnicity. There appeared to be disparate service use among US samples in terms of ethnicity and socio-demographic status, regardless of type of health insurance provision s- this may be explained by underlying differences in health-seeking behaviours. Overall, use of follow-up care appeared to be lower than expected and barriers existed for particular groups of cancer survivors. Conclusions Studies focussed on the use of a specific type of service rather than adopting a whole-system approach and future health services research should address this shortcoming. Overall, there is a need to improve access to care for all cancer survivors. Studies were predominantly US-based focussing mainly on breast or colorectal cancer. Thus, the generalisability of findings to other health-care systems and cancer sites is unclear. The Andersen Behavioural Model provided an appropriate framework for studying and understanding health service use among cancer survivors. The active involvement of physicians and use of personalised care plans are required in order to ensure that post-treatment needs and recommendations for care are met.